GARCH modeling of robust market returns - Lucía Cuadro-Sáez; Manuel Moreno (Kiel Institute for the World Economy (IfW), 2007)
Daily financial market returns (as log difference in closing prices) may be quite sensitive to operation with low trading volumes and big changes in prices frequently traded at market closing times. This paper proposes a more robust estimation of market returns by providing a new indicator that accounts for the information content in prices and trading volumes: the volume weighted return. Then, we estimate a GARCH (1,) model for the IBEX-35 futures market that includes shocks arising from countries linked to the Spanish economy. Our empirical findings suggest that the impact of the relevant news coming from abroad and thus, it might be relevant to assess the linkage of one market to other economies.
Keywords: G14; G15; G10; 330; volume weighted return; trading volumes; international transmission of news; GARCH; Kapitalertrag; Börsenkurs; Börsenumsatz; Internationaler Preiszusammenhang; Informationsverbreitung; ARCH-Modell; Theorie; Spanien; Welt